Synthesis and Characterization of Biodegradable Plastic from Tropical Marine Microalgae Navicula sp. TAD01 - Ivon Telussa; Matheis F.J.D.P Tanasale; Ali Ridho Arif Madja (Postgraduate, University of Mataram, 2023)
The use of plastics made from petrochemicals has a bad environmental impact. One of the efforts to overcome this is using microalgae Navicula sp. as a raw material for making biodegradable plastics. Navicula sp. TAD01 is a type of marine microalgae that is spread Inner Bay of Ambon and can be used to manufacture biodegradable plastics. In this study, biodegradable plastic was synthesized from the biomass of Navicula sp. TAD01, characterization and degradation test. The method used in this research includes three stages. Navicula sp. TAD01 cells were grown in the first stage to obtain biomass. The second stage is making biodegradable plastic from the biomass of Navicula sp.Â TAD01. The last step is to characterize biodegradable plastics and perform a degradation test. Cultivation of Navicula sp. TAD01 obtained dry biomass of 6.4398 grams, with a productivity value of 0.0524 gL-1h-1. The biodegradable plastic made has a slippery texture and a greenish opaque color with a thickness of 0.05 mm. It has tensile strength and elongation values at break of 1.36 MPa and 30.7%, respectively. The results of the analysis of the biodegradation test on this biodegradable plastic film have a mass loss percentage value of 85.27% with an immersion time of 10 days. This shows that Navicula sp TAD01 has the potential to be used as an ingredient in the manufacture of biodegradable plastics that can degrade well